Statistical Treatments and Comparison between Normal Calibration and Ultimate Precision Methods in Spectrophotometric Determination of Aspirin in APC Tablets - Al-Qaisy H. Mayada (College of Pharmacy / Mustansiriyah University, 2005)
In this work a statistical comparison were carried out between two techniques, normal calibration (NC) and ultimate precision (UP) technique, for the spectrophotometric determination of Aspirin (acetyl salicylic acid) in APC tablets, where the second method provide a means of expanding the scale of readout limited instrument and decreasing error significantly. It was found that the relative error was decreased from 6% to 2% on using the UP technique with RSD of 0.86% and 0.54% for NC and UP technique, respectively, Where these data were calculated for synthetic sample with knownconcentration. The 95 % confidence limit was also calculated for NC and UP methods. An equation was also derived for direct calculation of concentration of unknown from UP technique. Where this equation could be applied for most spectrophotometric determination of sample by UP procedure.